A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India - Komai, Tomoyuki; Ravinesh, Raveendhiran; Kumar, Appukuttannair Biju (Zootaxa, 2018)
A new species of the hermit crab genus Diogenes Dana, 1851, D. spongicola, is described and illustrated on the basis of material collected from two locations off southern India. It appears close to D. takedai Rahayu, 2012 among about 70 congeners, but easily differentiated from the latter by the spinulose anterolateral margins of the shield, the article 2 of the antennal peduncle armed only with one distal spine, the longer, spinose antennal acicle, the absence of prominent spines on the ventrolateral margin of the cheliped meri, and the different color of the cheliped palm. Specimens of the new species were all collected from cavities of a callyspongiid sponge Callyspongia diffusa (Ridley, 1884), suggesting a possible association between the hermit crab and sponge.